KEUTAMAAN MEMBACA - Faiz Fadhli; Tamam, Faisal Fathun, Muzaki Mubarok, Nurfitri (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Indonesia's national education is still facing various problems. The achievements of educational outcomes have not met expectations. Learning in schools has not been able to fully shape graduates who reflect the character and culture of the nation. The development of education based on the character and culture of the nation needs to be a national programme. Because with knowledge, new discoveries will be made that can make human life better, easier and more prosperous. Science plays an important role in changing the civilisation of a nation. Therefore, by reading, we can broaden our horizons and knowledge. However, the reading culture in Indonesia is still low, so it needs to be motivated by this writing so that the reading culture of this country's people can increase, so that this country and nation can advance and win in this global competition.